2021
DOI: 10.3390/app11209422
|View full text |Cite
|
Sign up to set email alerts
|

Secure Outsourced Blockchain-Based Medical Data Sharing System Using Proxy Re-Encryption

Abstract: The security and privacy of electronic health records (EHRs) have received considerable attention from healthcare workers and researchers. To ensure security, various encryption and decryption schemes as well as key management protocols have been developed. However, owing to sharing and scalability issues, additional security technologies have been proposed. Nonetheless, these technologies cause other problems, such as efficiency issues. Blockchain-based EHR management systems have been proposed to overcome co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
(50 reference statements)
0
10
0
1
Order By: Relevance
“…• Invariabilidad de datos: así como es su ventaja, a su vez puede ser lo contrario, esto debido al momento en que las personas erran en registrar información, generando así problemas en la realidad, dado que los datos no podrán ser editada [22].…”
Section: Desventajas De La Tecnología Blockchainunclassified
“…• Invariabilidad de datos: así como es su ventaja, a su vez puede ser lo contrario, esto debido al momento en que las personas erran en registrar información, generando así problemas en la realidad, dado que los datos no podrán ser editada [22].…”
Section: Desventajas De La Tecnología Blockchainunclassified
“…However, the RSA asymmetric encryption algorithm has low efficiency, which affects system performance. Park et al (2021) proposed the Medchain architecture, which uses proxy re-encryption to protect patient privacy. The patient’s private data is re-encrypted by a cloud-based proxy server node, which is vulnerable to attacks and poses a single point of failure risk.…”
Section: Related Workmentioning
confidence: 99%
“…6 and 7 for encryption and decryption overhead of original data, respectively. Additionally, to test the performance of the proposed scheme during encryption and decryption of original data, it was compared to the schemes proposed by Dong et al (2020) and Park et al (2021) . Dong et al (2020) proposed the use of AES symmetric encryption algorithm, while Park et al (2021) suggested the use of proxy re-encryption technique for data privacy protection.…”
Section: Experiments and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…algorithms (Fu et al, 2021), and the distributed storage of data through P2P networks. Due to its advantages in decentralization and traceability and immutability, blockchain technology has been widely used in industries such as information sharing (Park et al, 2021), product traceability , copyright protection (Liu et al, 2021), supply chain (Pournader et al, 2020), and finance (Kowalski et al, 2021). Currently, the development of blockchain is divided into three stages: blockchain 1.0, blockchain 2.0, and blockchain 3.0.…”
mentioning
confidence: 99%